Water column dissolved nitrous oxide concentrations during SONNE cruise SO298 - Damian L Arévalo-Martínez; Hermann W Bange; Eric Pieter Achterberg; Mike M S M Jetten; Kassandra Kakkarou; Jannik Löhr; Zvi Steiner; Caroline P Slomp (PANGAEA, 2025)
The data set comprises concentrations of dissolved nitrous oxide (N2O) from seawater samples collected during the RV/Sonne cruise SO-298. The expedition took place between April 14th and June 2nd 2023, and focused on physical and biogeochemical conditions across the equatorial Pacific Ocean as part of the GEOTRACES program. Samples were collected by drawing water from a 10 L Niskin bottle into borosilicate 20 mL vials, which were then sealed with rubber (butyl) stoppers and aluminium caps. Immediately after collection, samples were preserved by adding 100 μL of a saturated mercuric chloride solution. Samples were analyzed by means of a standard headspace method coupled to gas chromatography/electron capture detection (see e.g. Wilson et al., 2018; https://doi.org/10.5194/bg-15-5891-2018).